Shore Platform Processes in Eastern Canada - Trenhaile, Alan; Porter, Neil; Kanyaya, Jacob (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThis research is conducted on a mesotidal, argillite shore platform at Mont Louis in Gaspé, Québec, and on macrotidal platforms in the basalts of Scots Bay and the sandstones of Burncoat Head in Nova Scotia. Rock samples have been subjected to wetting and drying and to salt weathering cycles. The platforms were surveyed; rock hardness was determined with a Rock Test Hammer; waves were recorded in the field; and downwearing rates were measured at 56 micro-erosion meter stations over 1 to 3 years. Weathering is the dominant process at Mont Louis, although the horizontal platform may have been cut by waves at the high tidal level. Wave backwearing was much more important than downwearing by weathering during the Holocene at Scots Bay. Wave quarrying only occurs on a few scarps today, however, and without much abrasive material, slow downwearing now dominates over most of the platform surface. Waves probably help to remove loosened sand grains at Burncoat Head, thereby contributing to platform downwearing. Abrasion is also important in places, but the data suggest that backwearing by wave quarrying and probably frost has been a little more important than downwearing by abrasion and weathering during the Holocene.